?SYNTHESIS OF NITROGENOUS COMPOUNDS.Part -V - MOKHTAR, H.M.; FARAHAT, 0.0. (Biological Sciences - PJSIR, 1995)
Condensation of 3,4-disubstituted-but-3-en-2-ones (3) with hydrazines produced the hydrazones (4) which with ethanolic HCI underwent cyclization to the pyrazolines (5). Oxidation of (5) with bromine-water furnished the pyrazoles (6). Similarly, condensation of (3) with acylhydrazines generated the acylhydrazones (7). Ethyl 6-aryl-2, 4-dioxo-5-substituted hexenoates (8) has been synthesized by condensation of 3,4-disubstituted- but-3-en-2-ones (3) with ethyl oxalate. Esters (8) on reaction with hydroxylamine afforded the isoxazole esters (9), whereas, with acylhydrazines furnished the acylhydrazones (lO) which were cyclized to N-acylpyrazoles (11). With hydrazines, compounds (8) underwent cyclization to the pyrazole esters (12) which were converted either to the acids (13; R2= OH) or to the acid hydrazides (13; R2= NHNH2). Reaction of (12; R'= C6H4S02NH2(p» with the appropriate isothiocyanate derivatives produced benzenesulphonylthioureas which with ethyl bromo acetate and ethyl ~-bromopro- pionate furnished 2-iminothiazolidinones (15) and 2-iminothiazinones (16) respectively. Moreover, esters (8) with 0- phenylenediamine yielded the oxyquinoxalines (17).